2018
DOI: 10.2478/folmed-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Olive Oil on the Rats’ Cerebellum: Functional and Structural Evidence

Abstract: Background: Olive oil is a food additive and used in many biological studies as a solvent for other chemicals, including drugs. Aim: The present study aimed to investigate the effects of olive oil on rats’ cerebellum structure and motor function. Materials and methods: Male rats were randomly divided into two groups orally receiving distilled water and olive oil (1 ml/kg/day). At the end of week 4, motor function was assessed in the rotarod test. The cerebellum was removed for stereo-logical assessment. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
2
8
0
2
Order By: Relevance
“…Moreover, body injuries and lesion on the back and tail of mice have been seen in the all groups of SB treated compare with the control, and they may be a result of aggressive and fighting behavior, in agreement with the previous reports by Noorafshan et al …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, body injuries and lesion on the back and tail of mice have been seen in the all groups of SB treated compare with the control, and they may be a result of aggressive and fighting behavior, in agreement with the previous reports by Noorafshan et al …”
Section: Discussionsupporting
confidence: 92%
“…Benzoic acid and SB are extensively used preservatives in dietary food products, but chronic exposure in vivo studies to evaluate their effects are limited to report about reduced growth and feed intake in mice and rats . Furthermore, short time exposure caused some harmful effects on rat liver and kidney functions, anxiety, and motor impairment in rats …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebellar total volume has been stereologically assessed in humans, with males presenting a value of 120.5 ± 11.1 cm 3 , and females a value of 105.9 ± 11.2 cm 3 (Taman, Kervancioglu, Kervancioglu, & Turhan, 2019). The corresponding published values for rabbits (Karabekir et al, 2014) and rats (Noorafshan, Asadi-Golshan, Erfanizadeh, & Karbalay-Doust, 2018) are 0.69 ± 0.03, and 0.08 ± 0.004 cm 3 for the volume of each cerebellar hemisphere, respectively. If analysing the mean volumetric data reported above for the cerebella of the various species, it can be observed that the cat cerebellum presents a larger relative volume in relation to average body size for the species, in comparison with the rabbit and the rat.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar total volume has been previously assessed by stereological techniques in other species such as humans, which exhibited a difference between sexes, with male cerebella measuring 120.5 ± 11.1 cm 3 in volume, while females 105.9 ± 11.2 cm 3 (Taman et al, 2020). Cerebellar volume has also been stereologically estimated in rabbits (Karabekir et al, 2014) and rats (Noorafshan et al, 2018), presenting volumes of 0.69 ± 0.03 cm 3 , and 0.080 ± 0.004 cm 3 for each cerebellar hemisphere, respectively, but also in cats (Sadeghinezhad et al, 2020), presenting a mean cerebellar hemisphere volume of 2.06 ± 0.29 cm 3 . When comparing total cerebellar volume (in cm 3 ) in relation to body weight (in kg) in each species, it appears that the guinea pigs of the present study have a cerebellar volume to body weight ratio of 0.9, which is consistent with the 0.8 calculated for the rat (Noorafshan et al, 2018), but greater than the 0.4 estimated for the rabbit (Karabekir et al, 2014), and less than an approximate 1.7 for an adult individual of average weight (Taman et al, 2020) and than the approximate 1.1 calculated for a medium‐sized cat (Sadeghinezhad et al, 2020).…”
Section: Discussionmentioning
confidence: 99%